2008
DOI: 10.1097/ede.0b013e318176bfcd
|View full text |Cite
|
Sign up to set email alerts
|

Heat Effects on Mortality in 15 European Cities

Abstract: There is an important mortality effect of heat across Europe. The effect is evident from June through August; it is limited to the first week following temperature excess, with evidence of mortality displacement. There is some suggestion of a higher effect of early season exposures. Acclimatization and individual susceptibility need further investigation as possible explanations for the observed heterogeneity among cities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
599
5
21

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 749 publications
(675 citation statements)
references
References 30 publications
50
599
5
21
Order By: Relevance
“…Previous studies reported that temperature-related mortalities are more pronounced in the elderly (Revich and Shaposhnikov 2008;Anderson and Bell 2009). However, the heterogeneity among different age groups is worth further examination (Hajat et al 2007;Baccini et al 2008;Ishigami et al 2008). In this study, we investigated both effects of heat and cold temperatures on different types of mortality (including non-accidental, cardiopulmonary, cardiovascular, and respiratory) and age-specific non-accidental mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that temperature-related mortalities are more pronounced in the elderly (Revich and Shaposhnikov 2008;Anderson and Bell 2009). However, the heterogeneity among different age groups is worth further examination (Hajat et al 2007;Baccini et al 2008;Ishigami et al 2008). In this study, we investigated both effects of heat and cold temperatures on different types of mortality (including non-accidental, cardiopulmonary, cardiovascular, and respiratory) and age-specific non-accidental mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Amaury de Souza (1) Flavio Aristone (1) Luciane Fernandes (1) Li Bai (2) Weiwei Yu (3) Débora Aparecida da Silva Santos (1) Ismail Sabba (4) ingresos por enfermedades respiratorias y franja de edad. Las mayores medias de ingreso se dieron en la franja de …”
Section: Artigo Originalunclassified
“…This lag is consistent with the lag modeling done using the DLNM testing of the mortality data (not shown). Minimum temperatures represent a measure that has been highlighted in earlier research (BACCINI et al 2011;BACCINI et al 2008). The theoretical explanation for the impact of high minimum temperatures on health is that this temperature represents the level of physiological respite from heat that an organism gets at night.…”
Section: The Formula For Calculating the Relaic For Model I Is: Exp((mentioning
confidence: 99%
“…The analytical method chosen was a good fit for the project, as it was well adapted to the data available (only cases, limited cofactors) and an estimate of the exposure effect in Barcelona is not needed, as this work has already been done (MATTHIES & MENNE 2009;BACCINI et al 2011;BACCINI et al 2008;SAÉZ et al 2000). Because the available, spatially located mortality data had only two cofactors (age and sex), modeling interactions would have been limited, even using a more complex analytical methodology.…”
Section: Appropriateness Of a Case-only Design For This Studymentioning
confidence: 99%